Exploring Relationships between Physiological and Psychological Condition of Seniors and Their Mobility and Social Activity. Issue 1 (January 2015) - Chen, Wan-Hui; Lin, Wan-I; Chang, Sheng-Hsiung; Mak, Long-Ching
Taiwan will become a super-aged society by 2025, and promoting active and healthy aging for seniors is desired. This study investigated the relationship between the physiological and psychological condition of seniors and their transportation mobility in relation to their social activities. Mobility was measured by trip frequency and classified into three types: outdoor exercise, chatting with neighbors, and longer-distance activities. The analysis results showed that of the 1, 223 subjects, 274 (22.4%) had depressive symptoms, and 252 (20.6%) had poor leg mobility. Analysis results of negative binomial models showed that seniors with depression, leg mobility problems, or both had a lower frequency of the three types of social activity trips. Other factors affecting frequency of social activity by seniors included eye problems, age, education level, motorcycle availability, and types of areas where subjects lived. With consideration of trip patterns for seniors with depression and leg mobility problems, this study offers certain improvement strategies. For example, because seniors prefer active transportation modes, promoting an innovative three-wheeled electric auxiliary bicycle is suggested. Seniors who rode motorcycles and lived in suburban or rural areas had higher frequencies of trips for longer-distance activities. Motorcycles can help seniors maintain their mobility; however, motorcycles are a high-risk mode of travel, especially for seniors. Motorcycle safety for seniors is an issue in Taiwan. In addition, there was an obvious preference by depressed elderly people for religious activities. Religious venues are good places to attract seniors for social activities and to communicate the benefits of an active lifestyle.